Development of an inducible transposon system for efficient random mutagenesis in Clostridium acetobutylicum - Zhang, Ying; Xu, Shu; Chai, Changsheng; Yang, Sheng; Jiang, Weihong; Minton, Nigel P.; Gu, Yang (Oxford University Press, 2016)
Clostridium acetobutylicum is an industrially important Gram-positive organism which is capable of producing economically important chemicals in the ABE (Acetone, Butanol and Ethanol) fermentation process. Renewed interests in the ABE process necessitate the availability of additional genetics tools to facilitate the derivation of a greater understanding of the underlying metabolic and regulatory control processes in operation through forward genetic strategies. In this study, a xylose inducible, mariner-based, transposon system was developed and shown to allow high-efficient random mutagenesis in the model strain ATCC 824. Of the thiamphenicol resistant colonies obtained, 91.9% were shown to be due to successful transposition of the catP-based mini-transposon element. Phenotypic screening of 200 transposon clones revealed a sporulation-defective clone with an insertion in spo0A, thereby demonstrating that this inducible transposon system can be used for forward genetic studies in C. acetobutylicum.